Diastereo- and Facially Selective Imino-Diels–Alder Cycloaddition of 2-Azeditinone-Tethered 1-Azadiene: Synthesis of Functionalized (2-Oxo-4-styrylazetidin-3-yl)–Pyridine Hybrids - Kumar, Yogesh; Singh, Prabhpreet; Bhargava, Gaurav (Synlett, 2015)
Highly diastereo- and π-facially selective imino Diels–Alder cycloadditions of 3-allylideneamino-2-azetidinones having stereocentres at its α- and β-positions, with symmetrical dienophiles leading to the formation of biologically potent (2-oxo-4-styrylazetidin-3-yl)–pyridine hybrids have been reported.
Keywords: Diels–Alder reactions; diastereoselectivity; π-facial selectivity; β-lactams; 1-azadiene